PERANCANGAN FRAMEWORK GREEN IT UNTUK MENGURANGI DAMPAK NEGATIF DALAM ORGANISASI: Green IT, E-Waste, Energy Management, Organizations - Muttaqi, Fajar; Alfaujianto, Moh.; Surahmat, Asep (LP2M Universitas Nurdin Hamzah, 2025)
The adoption of technological advancements has strengthened the role of information technology (IT) in organizational operations. While IT provides various benefits, it also creates environmental challenges, such as high energy consumption and increasing electronic waste (e-waste). The International Energy Agency (IEA) reports that data centers and IT networks consume 1% of global energy, yet only 17.4% of e-waste is recycled. Therefore, a sustainable IT management approach is crucial. Green IT integrates sustainability principles into IT management to improve energy efficiency, waste reduction, and eco-friendly technology adoption. However, challenges such as unclear guidelines, infrastructure limitations, and low organizational awareness hinder its implementation. This study aims to design a Green IT framework suited to Indonesia’s context, using literature reviews, stakeholder interviews, and case studies. The findings will provide organizations with structured guidance to reduce environmental impact, improve efficiency, and enhance competitiveness in the digital era